Adverse effects of medicinal plants used by cancer patients in Beni Mellal and the communication of this use - Aboufaras Mohamed (EDP Sciences, 2021)
Moroccan cancer patients use traditional herbal medicine and no ethno botanical study has targeted them in the Béni Mellal Khénifra region. We had the objective to measure the frequency use of medicinal plants by cancer patients in the region of Béni Mellal Khénifra as well as the communication around this use and to inventory the plants used added to their adverse effects. We used an ethno botanical survey was conducted among 314 patients at the regional oncology center of Béni Mellal. The prevalence of use and the relative frequency of citation (RFC), the proportion of patients reporting this use and its adverse effects were measured. the prevalence of medicinal herbs use was 37.3% (n = 117). The citation relative frequency of plants ranged from 0.005 to 0.16. We found, also, 32 species belonging to 19 botanical families. Almost 90% (n = 102) of patients do not communicate this use and the most used plants are: Marrubium vulgare (16%), Ephedra alata (13%) and Juniperus oxycedrus (12%) Some plants seem toxic, in particular Juniperus oxycedrus used in a form of tar. The drug-plant interaction requires monitoring due to the lack of communication.